The interaction of the Chrna5 D398N variant with developmental nicotine exposure - O’Neill, Heidi C. (Genes Brain Behav, 2018)
A single nucleotide polymorphism (SNP) in CHRNA5 (rs16969968, change from an aspartic acid (D) to asparagine (N) at position 398 of the human α5 nicotinic acetylcholine receptor subunit) has been associated with increased risk for nicotine dependence. Consequently, carriers of the risk variant may be at elevated risk for in utero nicotine exposure. To assess whether this gene-environment interaction might impact nicotine intake in developmental nicotine-exposed offspring, we utilized a mouse expressing this human SNP. D and N dams drank nicotine (100 μg /ml) in 0.2% saccharin water or 0.2% saccharin water alone (vehicle) as their sole source of fluid from 30 days prior to breeding until weaning of offspring. The nicotine (D Nic, N Nic) or vehicle (D Veh, N Veh) exposed offspring underwent a two-bottle choice test between postnatal ages of 30–46 days. N Nic offspring consumed the most nicotine at the highest concentration (400 μg/ml) compared to all other groups. In contrast, D Nic offspring drank the least amount of nicotine at all concentrations tested. Nicotine-stimulated dopamine (DA) release measured from striatal synaptosomes was increased in D Nic offspring, while decreased in N Nic offspring relative to their genotype-matched controls. These data suggest that the α5 variant influences the effect of developmental nicotine exposure on nicotine intake of exposed offspring. This gene-environment interaction on striatal DA release may provide motivation for increased nicotine seeking in N Nic offspring and reduced consumption in D Nic offspring.